2012
DOI: 10.3109/14767058.2012.733766
|View full text |Cite
|
Sign up to set email alerts
|

The severity of hypoxic changes and oxidative DNA damage in the placenta of early-onset preeclamptic women and fetal growth restriction

Abstract: Our findings indicate that the severity of hypoxic changes and oxidative DNA damage are greater in the placenta of women with early-onset preeclampsia, and that the prolonged preeclamptic conditions may reduce placental blood flow, ultimately leading to FGR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 41 publications
1
33
0
3
Order By: Relevance
“…Damage caused by oxidative stress, including changes to DNA and proteins, as well as the mechanisms of DNA repair, appears to play a key role in obstetrical pathologies of placental origin, including PE and IUGR (Vascotto et al 2007;Takagi et al 2004;Kimura et al 2013;Rossi et al 2013;Tamura et al 2011). In this paper, we also focus our attention on the immunohistochemical expression of APE1/ Ref-1 (APE1).…”
Section: Introductionmentioning
confidence: 99%
“…Damage caused by oxidative stress, including changes to DNA and proteins, as well as the mechanisms of DNA repair, appears to play a key role in obstetrical pathologies of placental origin, including PE and IUGR (Vascotto et al 2007;Takagi et al 2004;Kimura et al 2013;Rossi et al 2013;Tamura et al 2011). In this paper, we also focus our attention on the immunohistochemical expression of APE1/ Ref-1 (APE1).…”
Section: Introductionmentioning
confidence: 99%
“…HIF-1α and 8-OHdG staining in nuclei of the placental trophoblast in early-onset preeclamptic women was significantly greater than in late-onset preeclamptic women. 20) These results indicate that under prolonged preeclamptic conditions in early-onset disease, long-term exposure to preeclamptic conditions impairs uterine artery flow, reduces blood flow to the placenta, causes placental oxidative DNA damage, and ultimately leads to FGR. In the present study, we demonstrated that oxygen free radical production is increased without change of antioxidants in the fetus in preeclamptic women with FGR.…”
Section: Discussionmentioning
confidence: 94%
“…If 0% of the cells was stained, the score was 0; 1, <10 was 1, 11-25% was 2; 26-50% was 3, and 51-100% was 4. According to the product of the two variables, the samples were categorized as follows: negative (-), 0-3; mildly positive (+), 4-6; moderately positive (++), 7-9; and strongly positive (+++), [10][11][12].…”
Section: Evaluation Of the 8-ohdg P-src And P-egfr Resultsmentioning
confidence: 99%
“…Oxidative DNA damage plays crucial roles in the pathogenesis of numerous diseases, including cancer. 8-hydroxy-2′-deoxyguanosine (8-OHdG) is the most representative product of oxidative modifications of DNA and can be used as a biomarker for oral cancer screening [11]. Therefore, the current study used the immunohistochemistry (IHC) SP method to detect the expressions of 8-OHdG, p-Src, and p-EGFR in TSCC and its adjacent tissues; analyzed their relationships and correlations; and preliminarily explored the mechanism of ROSmediated activation of an EGFR signaling pathway to provide information for further studies on the effectiveness of targeted drug treatments in oral cancer.…”
Section: Introductionmentioning
confidence: 99%